Rest in God − The Spirituality of Rest - Ivan Platovnjak (Edinost in Dialog, 2022)
Rest does not seem to have the same prominent place in Christian spirituality as prayer and the celebration of the sacraments, since there is almost no direct scientific research on it. Is it really self-evident that a Christian rests and does not need to be encouraged to do so? In our time, when there is much talk of overwork and burnout, it is necessary to explore this area so as to shed light on it from the perspective of the Christian spiritual life. Too often a mentality prevails that heaven has to be earned through constant work and that we never do enough. This raises the question of whether Christians have a correct understanding of Jesus and the good news he brought into this world, as well as of his life and ministry, which should reflect in their lives and ministries. The author puts forward the thesis that a Christian cannot live his spirituality fully if there is no place for rest or rest in God. In fact, rest is the identifying mark of authentic Christian spirituality, which always includes a spirituality of rest. In the article, the author first shows how the understanding of work as merit hinders the relationship with God. Then he illustrates how being with Jesus Christ is a source of rest. In the last section, he briefly reviews different forms of rest in God that make it possible to live a spirituality of rest.